Fluorescein tear break-up time in Malays - Norhani Mohidin; Amran Hj. Ramli (penerbit ukm, 2004)
Eye care practitioners routinely use the fluorescein tear break-up time (TBUT) as one of the tests for diagnosing dry eye. The cut off value is normally taken from data presented from western population studies. To our knowledge the mean fluorescein TBUT of a Malay population has not been reported. In this paper we report the mean value of the fluorescein TBUT in a sample of Malay population and its effect with an increase in age. Our results showed that the mean TBUT value in Malays is much less than established values reported for Caucasian populations. Eye care practitioners should take this value into account when faced with the diagnosis of dry eye.